2023
DOI: 10.1136/bmjopen-2023-072762
|View full text |Cite
|
Sign up to set email alerts
|

What works for and what hinders deimplementation of low-value care in emergency medicine practice? A scoping review

Vinay Gangathimmaiah,
Natalie Drever,
Rebecca Evans
et al.

Abstract: ObjectivesLow-value care can harm patients and healthcare systems. Despite a decade of global endeavours, low value care has persisted. Identification of barriers and enablers is essential for effective deimplementation of low-value care. This scoping review is an evidence summary of barriers, enablers and features of effective interventions for deimplementation of low-value care in emergency medicine practice worldwide.DesignA mixed-methods scoping review was conducted using the Arksey and O’Malley framework.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 177 publications
0
2
0
Order By: Relevance
“…The challenges of providing care in this time-, space-, staff-and information-constrained setting can lead to LVC. 9 Similar to metropolitan settings, we have identified that approximately a third of urine cultures, coagulation studies, blood cultures and cranial CT scans conducted within the TUH-ED setting, may be seen as low value. 10,11 Recent semi-structured interviews with TUH-ED clinicians identified LVC is fuelled by perceptions of efficiency further compounded by clinician beliefs about consequences and capabilities of care provision (unpublished data).…”
Section: Health System Resourcesmentioning
confidence: 79%
See 1 more Smart Citation
“…The challenges of providing care in this time-, space-, staff-and information-constrained setting can lead to LVC. 9 Similar to metropolitan settings, we have identified that approximately a third of urine cultures, coagulation studies, blood cultures and cranial CT scans conducted within the TUH-ED setting, may be seen as low value. 10,11 Recent semi-structured interviews with TUH-ED clinicians identified LVC is fuelled by perceptions of efficiency further compounded by clinician beliefs about consequences and capabilities of care provision (unpublished data).…”
Section: Health System Resourcesmentioning
confidence: 79%
“…Amidst a national context of emergency department overcrowding 7,8 the Townsville University Hospital Emergency Department (TUH‐ED) cared for 99 748 people in 2024. The challenges of providing care in this time‐, space‐, staff‐ and information‐constrained setting can lead to LVC 9 . Similar to metropolitan settings, we have identified that approximately a third of urine cultures, coagulation studies, blood cultures and cranial CT scans conducted within the TUH‐ED setting, may be seen as low value 10,11 .…”
Section: Reduced Regional Health System Resourcesmentioning
confidence: 87%